AN EVALUATION OF DIAMOND HEALTH PROMOTING SCHOOL PROJECT OF CHUMCHON BAN PAFAEK SAMAKKHI SCHOOL UNDER THE PHAYAO PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Chaipin, Nithit (Journal of Buddhist Anthropology, 2022)
This objectives an evaluation of research article were to evaluate the context, the input, the process and the products of diamond health promoting school project of Chumchon Ban Pafaek Samakkhi School under the Phayao Primary Educational Service Area Office 1 by using CIPP model. The target group of 142 people was derived from specific selection consist of teachers, school committee, community leaders, local politicians, hospital staffs, parents and students, Research tools were questionnaires using a 5-level estimation scale and statistics used were percentage, mean and standard deviation. The findings showed that: 1) Context: needs, compliance with the policy of the agency and in accordance with the objectives of the project overall and each side has passed the evaluation criteria at the highest level. ( = 4.82, S.D. = 0.33). 2) Input: personnel, management, place, community participation, media and equipment and budget overall has passed the evaluation criteria at the highest level ( = 4.62, S.D. = 0.48). 3) Process: Plan, Do, Check, Act has passed the evaluation criteria at the highest level. ( = 4.83, S.D. = 0.32). And 4) Product : (1) the project evaluation result of the Diamond Health Promotion School criteria in the academic year 2020 has 3 passed, 19 indicators and (2) the projects’ satisfaction evaluation in the overall was at the highest level ( = 4.77, S.D. = 0.38).